Agricultural Research Management - Loebenstein, G.; Thottappilly, G. (Springer Netherlands : Imprint: Springer, 2007)
Agricultural research is one of the most widespread forms of organized research in the world, in both developed and developing countries. Management of agricultural research involves many decisions that have scientific, social and political consequences. Every country has established agricultural research priorities based on many complex factors that must be considered when decisions are made on the choice of research problems to be investigated. Resources must be divided among projects that often compete for the limited funding available that supports the total research enterprise. This book will provide those individuals who manage research with methods and procedures that can be used in their management organization.